First-year students’ academic motivation during the pandemic: The role of social support and basic psychological needs - Čuljak, Lora; Pravica, Maja; Butković, Ana (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
Due to the COVID-19 pandemic, academic institutions needed to make swift changes in educational systems. Students needed to adapt and cope with novel challenges, which affected their academic motivation. Research shows that social support and satisfaction of basic psychological needs play an important role in maintaining academic motivation. The current study aimed to explore the role of perceived social support and satisfaction of basic psychological needs in first-year students’ academic motivation. Our sample included 117 first-year students who completed the Academic Motivation Scale, Social Support Assessment Scale, and Basic Psychological Need Satisfaction and Frustration Scale. Results showed positive associations of perceived social support from professors, satisfaction of needs for autonomy and relatedness, and autonomy frustration with intrinsic academic motivation. We used hierarchical regression analysis to better understand these associations and found that satisfaction of the need for autonomy was the most important predictor of intrinsic academic motivation, and it also fully mediated the association between social support received from professors and intrinsic academic motivation. Our findings highlight the importance of autonomy-supportive learning opportunities and professors’ support.